Clinical characteristics and factors associated with hospital admission or death in 43 103 adult outpatients with coronavirus disease 2019 managed with the Covidom telesurveillance solution: a prospective cohort study. (August 2021) - Yordanov, Youri; Dinh, Aurélien; Bleibtreu, Alexandre; Mensch, Arthur; Lescure, François-Xavier; Debuc, Erwan; Jourdain, Patrick; Jaulmes, Luc; Dechartres, Agnes; ,
Abstract: Objectives: Studies on coronavirus disease 2019 (COVID-19) have mainly focused on hospitalized patients or those with severe disease. We aim to assess the clinical characteristics, outcomes and factors associated with hospital admission or death in adult outpatients with COVID-19. Methods: This is a prospective cohort of outpatients with suspected or confirmed COVID-19, registered in the Covidom telesurveillance solution for home monitoring of patients with COVID-19 in the Greater Paris area, from March to August 2020. The primary outcome was clinical worsening, defined as hospitalization or death within 1 month after symptom onset. Results: Among 43 103 patients, mean age was 42.9 years (SD 14.3 years); 93.0% ( n = 40 081) of patients were <65 years old and 61.9% ( n = 26 688) were women. Of these 43 103 patients, 67.5% ( n = 29 104) completed a medical questionnaire on co-morbidities and symptoms. The main reported co-morbidities were asthma (12.8%; n = 3685), hypertension (12.3%; n = 3546) and diabetes (4.8%; n = 1385). A small proportion of all eligible patients (4.1%, 95% CI 3.9–4.2; 1751/43 103) experienced clinical worsening. The rate of hospitalization was 4.0% (95% CI 3.8%–4.2%; n = 1728) and 0.1% (95% CI 0.1%–0.2%; n = 64) died. Factors associated with clinical worsening were male sex, older age, obesity and co-morbidities such as chronic renal disease or cancer under treatment. Probability of worsening was reduced with anosmia/ageusia. Conclusions: Clinical worsening was rare among outpatients. Male sex, older age and co-morbidities such as chronic renal disease, active cancers or obesity were independently associated with clinical worsening. However, our cohort may include patients younger and healthier than the general population.